Sentencing and human rights : the limits on punishment - Summers, Sarah J. (Oxford : Oxford University Press, 2022)
'Sentencing and Human Rights' develops a systematic account of the importance of human rights principles at sentencing stage. It examines how principles of legality, proportionality, equality, and judicial responsibility may be expected to limit sentencing practices and suggests that the concept of state punishment needs to be reconsidered.
This edition also issued in print: 2022.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Title page verso.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Sentences (Criminal procedure); Human rights; Proportionality in law; Punishment; Law; Laws of specific jurisdictions & specific areas of law